Umbilical Cord Blood Cells Do Not Reduce Ventilation-Induced Lung Injury in Preterm Lambs - Smith, Madeleine J.; Chan, Kyra Y. Y.; Papagianis, Paris; Nitsos, Ilias; Zahra, Valerie; Allison, Beth; Polglase, Graeme R.; McDonald, Courtney A. (Frontiers in Physiology, 2020)
BACKGROUND: Preterm infants often have immature lungs and, consequently, many require respiratory support at birth. However, respiratory support causes lung inflammation and injury, termed ventilation-induced lung injury (VILI). Umbilical cord blood (UCB) contains five cell types that have been shown to reduce inflammation and injury. The aim of this study was to determine whether UCB cells can reduce VILI in preterm lambs. METHODS: We assessed lung inflammation and injury, with and without UCB cell administration. Fetal lambs at 125±1 days gestation underwent sterile surgery and were randomly allocated to one of four groups; unoperated controls (UNOP), sham controls (SHAM), injuriously ventilated lambs (VILI) and injuriously ventilated lambs that received UCB cells via the jugular vein 1 hour after ventilation (VILICELLS). Ventilated lambs received an injurious ventilation strategy for 15 minutes, before they were returned to the uterus and the lamb and ewe recovered for 24h. After 24h, lambs were delivered via caesarean section and euthanized and the lungs were collected for histological and molecular assessment of inflammation and injury. RESULTS: VILI led to increased immune cell infiltration, increased cellular proliferation, increased tissue wall thickness and significantly reduced alveolar septation compared to controls. Further, extracellular matrix proteins collagen and elastin had abnormal deposition following VILI compared to control groups. Administration of UCB cells did not reduce any of these indices. CONCLUSION: Administration of UCB cells 1 hour after ventilation onset did not reduce VILI in preterm lambs.